2020
DOI: 10.3390/su12198247
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Theoretical Constructs of a Green Lean Six Sigma Approach towards Environmental Sustainability: A Systematic Literature Review and Future Directions

Abstract: Green lean six sigma (GLSS) is an emerging approach towards environmental sustainability in conjunction with operational achievements. The success of this approach is premised on an understanding of the different components of a GLSS program; being the determinants for its outcomes. The aim of this paper is to investigate the various constructs of GLSS that play an essential role in achieving environmental sustainability. For this purpose, a systematic review of available literature has been conducted to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 105 publications
(253 reference statements)
0
43
0
Order By: Relevance
“…Therefore, researchers have emphasized an integrated GLSS approach as an environmental management strategy to overcome the drawbacks of GL and LSS combinations (Garza‐Reyes, 2015; Gholami et al, 2021). Such an integrated strategy can improve the environmental performance by identifying environmental impacts and removing waste, with common characteristics of waste reduction, value addition, and customer satisfaction (Farrukh et al, 2020; Gaikwad & Sunnapwar, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, researchers have emphasized an integrated GLSS approach as an environmental management strategy to overcome the drawbacks of GL and LSS combinations (Garza‐Reyes, 2015; Gholami et al, 2021). Such an integrated strategy can improve the environmental performance by identifying environmental impacts and removing waste, with common characteristics of waste reduction, value addition, and customer satisfaction (Farrukh et al, 2020; Gaikwad & Sunnapwar, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A scarcity of studies in this area calls for an investigation of motivational factors behind the adoption of GLSS and the overall trajectory a company would pursue towards improving its environmental performance. Further, a comparative analysis of drivers for environmental management between different countries is lacking in the literature (Belhadi et al, 2020; Farrukh et al, 2020). From this perspective, Cherrafi et al (2016) have highlighted this gap and emphasized comparative regional evaluation through an integrated model comprising strategies such as GLSS.…”
Section: Introductionmentioning
confidence: 99%
“…This added value to organizations so that they can better recruit and manage their employees. Farrukh et al (2020) investigated the various constructs of Green lean six sigma (GLSS). Findings showed that these constructs of GLSS as a holistic approach can facilitate an organization to better achieve environmental goals such as waste minimization, emission reduction, and resource conservation as compared to constructs of only one or any two of these strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the results of our study showed that these factors were crucial, based on experts' opinion. Farrukh et al (2020) found that a comprehensive GLSS strategy meets the necessities of environmental performance together with operational objectives. Their research results are also in line with our research results.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…It provides an operational framework in the company that explores and promotes problem solving [19]. Although the primary goal of this approach is not to reduce environmental waste, it is capable of improving environmental performance by lowering air emissions, energy consumption, and wastewater [20]. Technically, this methodology yields a failure rate of 3.4 parts per million [21].…”
Section: Introductionmentioning
confidence: 99%